WORKLOAD ANALYSIS TO OPTIMIZE WORKFORCE IN GLASS BOTTLE PACKING DIVISION USING FULL TIME EQUIVALENT METHOD - Shalsya Putri Desria; Rizka Britania; Amir Tjolleng (Fakultas Ekonomi Universitas Djuanda, 2026)
Perceived workload evaluation of employees in a company is crucial for optimizing workforce allocation and improving productivity. Improper workload assessment may lead to overburdened staff, burnout, and wasted resources. PT ABC, a company specializing in the production of glass bottles and glass blocks, has experienced workload imbalances that resulted in excessive strain that negatively impacts overall performance. This study aims to evaluate employee workload to optimize workforce allocation and improve productivity at PT ABC using Full-Time Equivalent (FTE) method. The company has 33 workers in various positions. The results categorized workloads into underload, normal, and overload categories. Overload was identified by manual packing operators. A tree diagram analysis was done to determine the root causes of overload, such as long processing times, large bottle sizes, high room temperatures, and inconsistent shift changes. Proposed solutions include increasing labor capacity, implementing palletizer machines, installing fans, and enforcing shift discipline.